Fundamentals of Neurologic Disease - Davis, M.D., Larry E.; Pirio Richardson, Sarah (Springer New York : Imprint: Springer, 2015)
This concise text delivers a basic introduction to neurology and is designed for use by medical students during their rotation in neurology and related disciplines. Updated and expanded, this second edition follows the same order as the first, starting with how to approach a patient with a neurologic problem followed by the latest information on the phenomenology, pathophysiology and symptoms of common adult and pediatric neurologic diseases.  Supplementing the learning experience are clinical cases that begin each chapter and videos of examples ranging from how to perform the normal neurologic exam to abnormal exam findings.    Easy-to-read and richly illustrated, Fundamentals of Neurologic Disease, 2nd Edition is an invaluable resource for anyone seeking to learn the fundamentals of neurology.